Polymer solid electrolyte and its manufacturing method

By integrating a single ion conductor and liquid phase POSS into the polymer electrolyte, the challenges of low ionic conductivity and stability are overcome, resulting in a safer and more efficient electrolyte with improved chain mobility.

JP2025501091APending Publication Date: 2025-01-17LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024537150
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-10-25
Filing Date
2023-10-20
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Conventional solid polymer electrolytes face challenges in achieving high ionic conductivity and stability due to the low mobility of lithium ions and anion accumulation, leading to battery performance deterioration and safety concerns.

Method used

Incorporating a single ion conductor and liquid phase polyhedral oligomeric silsesquioxane (POSS) into the polymer electrolyte structure to enhance polymer chain mobility and improve ionic conductivity.

Benefits of technology

The resulting polymer electrolyte exhibits enhanced safety and ionic conductivity, addressing the limitations of traditional electrolytes by improving chain mobility and reducing anion polarization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501091000001_ABST
    Figure 2025501091000001_ABST
Patent Text Reader

Abstract

The present invention relates to a polymer solid electrolyte, a manufacturing method thereof, and an all-solid-state battery including the same. More specifically, the present invention relates to a polymer solid electrolyte, and more particularly to a polymer solid electrolyte including a single ion conductor and a liquid-phase polyhedral oligomeric silsesquioxane (POSS) that can improve the fluidity of the polymer chains and simultaneously improve the safety and ionic conductivity of the polymer solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0138015 dated October 25, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.

[0002] The present invention relates to a polymer solid electrolyte and a method for producing the same. [Background technology]

[0003] Lithium secondary batteries that use liquid electrolytes have a structure in which the negative and positive electrodes are separated by a separator, and if the separator is damaged by deformation or external impact, a short circuit can occur, which can lead to risks such as overheating and explosion. Therefore, the development of a solid electrolyte that can ensure safety in the field of lithium secondary batteries is a very important issue.

[0004] Lithium secondary batteries using solid electrolytes have the advantages of improved battery safety and the prevention of electrolyte leakage, which improves battery reliability and makes it easier to manufacture thin batteries. In addition, because lithium metal can be used as the negative electrode, the energy density can be improved, and it is expected to be used in small secondary batteries as well as high-capacity secondary batteries for electric vehicles, and is attracting attention as a next-generation battery.

[0005] Among solid electrolytes, polymeric solid electrolytes may be made from ion-conductive polymer materials, and hybrid materials in which polymeric and inorganic materials are mixed have also been proposed. The inorganic material may be an inorganic material such as an oxide or sulfide.

[0006] Such conventional polymer solid electrolytes are manufactured through a process of forming a coating film and then drying it at a high temperature. However, the conventional manufacturing technology for polymer solid electrolytes has a limitation in that it is difficult to manufacture a polymer solid electrolyte with improved ionic conductivity due to the high crystallinity of crystalline polymers or semi-crystalline polymers.

[0007] In addition, polymer solid electrolytes are generally dual-ion conductors in which the lithium cations and the corresponding anions are all mobile. Here, the lithium ions are less mobile than the anions because they bind to the Lewis basic sites of the polymer matrix. Therefore, the lithium ion transport number of dual-ion conductors is generally 0.5 or less. In conventional polymer solid electrolytes, the lithium ions and the corresponding anions move in opposite directions during discharge, and the anions tend to accumulate on the negative electrode side, resulting in a concentration gradient and cell polarization, which can cause deterioration of battery performance if this phenomenon continues.

[0008] Meanwhile, single-ion conducting polymer solid electrolytes, which have anions fixed to the polymer chains, can exhibit a lithium ion transport number close to 1 and have no harmful effects on the anion polarization, so they have attracted much attention. However, it is very difficult for such single-ion conducting polymer solid electrolytes to have both high ionic conductivity and safety at the same time.

[0009] Therefore, there is a need to develop technology that can simultaneously ensure ionic conductivity and stability using single-ion conductive polymer solid electrolytes, which have recently attracted attention. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Korean Patent Publication No. 2017-0046995 Summary of the Invention [Problem to be solved by the invention]

[0011] As a result of extensive research to solve the above problems, the present inventors have confirmed that the stability and ionic conductivity of the polymer solid electrolyte are improved at the same time by adding a liquid phase polyhedral oligomeric silsesquioxane (POSS) to a single ion conductor to improve the chain mobility of the polymer chain.

[0012] Therefore, an object of the present invention is to provide a polymer solid electrolyte excellent in safety and ion conductivity, and a method for producing the same.

[0013] Another object of the present invention is to provide an all-solid-state battery including a solid polymer electrolyte having improved safety and ionic conductivity.

[0014] Another object of the present invention is to provide a battery module including the all-solid-state battery. [Means for solving the problem]

[0015] To achieve the above object, the present invention provides a polymer solid electrolyte comprising a single ion conductor and a liquid phase polyhedral oligomeric silsesquioxane (POSS);

[0016] The present invention also provides a method for producing a polymer solid electrolyte, the method including: (S1) forming a polymer solid electrolyte-forming solution containing a single ion conductor and a liquid-phase polyhedral oligomeric silsesquioxane (POSS); (S2) applying the polymer solid electrolyte-forming solution onto a substrate to form a coating film; and (S3) drying the coating film.

[0017] The present invention also provides an all-solid-state battery comprising the polymer solid electrolyte.

[0018] The present invention also provides a battery module including the all-solid-state battery. Effect of the Invention

[0019] The polymer solid electrolyte according to the present invention has a structure in which a polymer chain is entangled with a single ion conductor itself, and therefore exhibits excellent safety and ion conductivity.

[0020] In addition, the cage structure contained in the liquid-phase polyhedral oligomeric silsesquioxane (POSS) can improve the chain mobility of the polymer chain, thereby further improving the ionic conductivity. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a schematic diagram showing the internal structure of a polymer solid electrolyte according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] In the following, the present invention will be described in further detail to aid in understanding the invention.

[0023] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that is consistent with the technical idea of ​​the present invention, based on the principle that the inventor can appropriately define the concept of the term in order to explain his / her invention in the best possible manner.

[0024] Polymer solid electrolyte The present invention relates to a polymer solid electrolyte.

[0025] The polymer solid electrolyte according to the present invention includes a single ion conductor (SIC) and a liquid phase polyhedral oligomeric silsesquioxane (POSS). The polymer solid electrolyte may further include a lithium salt to further improve ion conductivity.

[0026] FIG. 1 is a schematic diagram showing the internal structure of a polymer solid electrolyte according to one embodiment of the present invention.

[0027] 1, the polymer solid electrolyte (1) may have a structure in which polymer chains contained in a single ion conductor (10) are entangled. The internal space formed by the polymer chains may contain liquid-phase polyhedral oligomeric silsesquioxane (POSS) (20), and a lithium salt (not shown) may also be contained in a dissociated state in the internal space.

[0028] In the present invention, the single ion conductor may be a fluorine-based polymer electrolyte membrane. Specifically, the single ion conductor includes a perfluorosulfonic acid (PFSA)-based polymer, and the sulfonic acid group (-SO 3 H) hydrogen is converted to lithium cation (Li +The single ion conductor has a structure in which the cations are substituted with lithium cations (Li + ) and therefore has excellent ionic conductivity. The perfluorosulfonic acid polymer may be Nafion (Dupont), Flemion (Asahi Glass), Aciplex (KRAsahi Kasei), or Aquivion (Merck).

[0029] The perfluorosulfonic acid polymer is suitable for use as a polymer electrolyte membrane due to its excellent mechanical stability, thermal stability and high ionic conductivity.

[0030] The single ion conductor may be contained in an amount of 20% by weight to 60% by weight based on the total weight of the polymer solid electrolyte, specifically, 20% by weight or more, 25% by weight or more, or 30% by weight or more, or 50% by weight or less, 55% by weight or less, or 60% by weight or less. If the content of the single ion conductor is less than 20% by weight, it is difficult to form a membrane-like polymer solid electrolyte, and if it exceeds 60% by weight, the content of the polyhedral oligomeric silsesquioxane in the liquid phase is relatively reduced, and the improvement effect of ion conductivity may be insignificant.

[0031] In the present invention, the liquid phase polyhedral oligomeric silsesquioxane (POSS) may be represented by the following chemical formula 1:

[0032] [ka]

[0033] In the above Chemical Formula 1, R are the same or different and are each independently selected from the group consisting of groups represented by the following chemical formulas 1-1 to 1-4:

[0034] [ka]

[0035] [ka]

[0036] [ka]

[0037] [ka]

[0038] In the above Chemical Formulas 1-1 to 1-4, L1 to L5 are C1 to C30 alkylene groups, R1 to R4 are selected from the group consisting of hydrogen; a hydroxy group; an amino group; a thiol group; a C1 to C30 alkyl group; a C2 to C30 alkenyl group; a C2 to C30 alkynyl group; a C1 to C30 alkoxy group; and a C1 to C30 carboxy group; m and n are the same or different and each independently represents an integer of 0 to 10; * indicates the bond position.

[0039] In addition, in the above chemical formulas 1-1 to 1-4, L1 to L5 are C1 to C10 alkylene groups, R1 to R4 are hydrogen, a hydroxyl group, or a C1 to C30 alkyl group, and m and n are the same or different and each independently an integer of 0 to 10.

[0040] In addition, in the above formula 1, R is selected from the group consisting of a polyethylene glycol group, a glycidyl group, an octasilane group, and a methacryl group.

[0041] Preferably, the polyhedral oligomeric silsesquioxane (POSS) may be a polyethylene glycol-polyhedral oligomeric silsesquioxane (PEG-POSS) in which R in Chemical Formula 1 is a polyethylene glycol group (PEG).

[0042] In addition, the liquid phase polyhedral oligomeric silsesquioxane (POSS) may be contained in an amount of 20 wt% to 60 wt% based on the total weight of the polymer solid electrolyte, and specifically, the content of the liquid phase polyhedral oligomeric silsesquioxane may be 20 wt% or more, 25 wt% or more, or 30 wt% or more, or 50 wt% or less, 55 wt% or less, or 60 wt% or less. If the content of the liquid phase polyhedral oligomeric silsesquioxane is less than 20 wt%, the effect of improving ion conductivity may be insignificant, and if it exceeds 60 wt%, the content of the single ion conductor may be relatively reduced, making it difficult to manufacture a membrane-shaped polymer solid electrolyte. In addition, within the above-mentioned weight range, the single ion conductor and the liquid phase polyhedral oligomeric siloxane may be included in a weight ratio of 1:1 to 1:2. If the weight ratio exceeds 1:1, the effect of improving ion conductivity may be insignificant, and if it is less than 1:2, phase separation may occur.

[0043] In the present invention, the lithium salt is contained in a dissociated state in the internal space of the polymer chain of the single ion conductor, thereby improving the ionic conductivity of the polymer solid electrolyte.

[0044] The lithium salt is (CF 3 SO 2 ) 2 NLi (Lithium bis(trifluoromethanesulphonyl)imide, LiTFSI), (FSO 2 ) 2 NLi (Lithium bis(fluorosulfonyl)imide, LiFSI), LiNO 3, LiOH, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 Cl 10 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, LiSCN and LiC(CF 3 SO 2 ) 3 may contain one or more selected from the group consisting of:

[0045] In addition, the lithium salt may be included in an amount of 10 wt% to 30 wt% based on the total weight of the polymer solid electrolyte, and specifically, the content of the lithium salt may be 10 wt% or more, 13 wt% or more, or 15 wt% or more, or 20 wt% or less, 25 wt% or less, or 30 wt% or less. If the content of the lithium salt is less than 10 wt%, the effect of improving ion conductivity may be negligible, and if it exceeds 30 wt%, there may be no benefit from increasing the content.

[0046] In the present invention, the polymer solid electrolyte may be in the form of a free-standing film or a coating layer. The free-standing film means a film that can maintain a film shape by itself without a separate support at room temperature and pressure. The coating layer means a layer obtained by coating on a substrate.

[0047] The free-standing film or coating layer has a characteristic as a support that stably contains lithium ions, and is therefore a suitable form for a polymer solid electrolyte.

[0048] In the present invention, the polymer solid electrolyte may further include a liquid electrolyte, which can further improve the ionic conductivity of the polymer solid electrolyte. The liquid electrolyte may also be contained in the internal space of the three-dimensional structure.

[0049] The liquid electrolyte may be a liquid electrolyte commonly used in the art, and the composition of the liquid electrolyte is not particularly limited as long as it can be used in a lithium secondary battery. For example, the liquid electrolyte may include a lithium salt and a non-aqueous solvent. The lithium salt may be any of the lithium salts described above. In addition, the non-aqueous solvent may include one or more selected from the group consisting of propylene carbonate (PC), ethylene carbonate (EC), vinylene carbonate (VC), diethyl carbonate (DEC), dimethyl carbonate (DMC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2MeTHF), dioxolane (DOX), dimethoxyethane (DME), diethoxyethane (DEE), γ-butyrolactone (GBL), acetonitrile (AN), and sulfolane.

[0050] The liquid electrolyte may be included in an amount of 1 to 5 wt % based on the total weight of the polymer solid electrolyte. If the content of the liquid electrolyte is less than 1 wt %, the effect of improving ion conductivity may be insignificant, and if it exceeds 5 wt %, the stability may be reduced.

[0051] Method for producing polymer solid electrolyte The present invention also relates to a method for producing a solid electrolyte, the method for producing the solid electrolyte includes the steps of: (S1) forming a polymer solid electrolyte forming solution containing a single ion conductor and a liquid-phase polyhedral oligomeric silsesquioxane (POSS); (S2) applying the polymer solid electrolyte forming solution onto a substrate to form a coating film; and (S3) drying the coating film. The polymer solid electrolyte forming solution may also be obtained by further using a lithium salt in the step (S1).

[0052] Hereinafter, each step of the method for preparing a solid electrolyte according to the present invention will be described in detail.

[0053] In the present invention, in the step (S1), a polymer solid electrolyte forming solution including a single ion conductor and a liquid phase polyhedral oligomeric silsesquioxane (POSS) may be formed. A lithium salt may be further added to increase ion conductivity. The types and contents of the single ion conductor, the liquid phase polyhedral oligomeric silsesquioxane (POSS) and the lithium salt are as described above.

[0054] Since the polyhedral oligomeric silsesquioxane (POSS) exists in a liquid phase at room temperature, the liquid polyhedral oligomeric silsesquioxane may be mixed with a single ion conductor to form a solution for forming a polymer solid electrolyte. A lithium salt may also be added.

[0055] In the present invention, in the step (S2), the polymer solid electrolyte forming solution can be applied onto a substrate to form a coating film.

[0056] The substrate is not particularly limited as long as it can serve as a support on which the polymer solid electrolyte forming solution is applied. For example, the substrate may be SUS (stainless steel), a polyethylene terephthalate film, a polytetrafluoroethylene film, a polyethylene film, a polypropylene film, a polybutene film, a polybutadiene film, a vinyl chloride copolymer film, a polyurethane film, an ethylene-vinyl acetate film, an ethylene-propylene copolymer film, an ethylene-ethyl acrylate copolymer film, an ethylene-methyl acrylate copolymer film, or a polyimide film.

[0057] In addition, the coating method is not particularly limited as long as it can coat the polymer solid electrolyte solution on the substrate in the form of a film, and may be, for example, bar coating, roll coating, spin coating, slit coating, die coating, blade coating, comma coating, slot die coating, lip coating, or solution casting.

[0058] In the present invention, in the step (S3), the coating film can be dried to obtain a polymer solid electrolyte.

[0059] all solid state battery The present invention also relates to an all-solid-state battery comprising the polymer solid electrolyte, the all-solid-state battery comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, and at least one of the positive electrode layer, the negative electrode layer, and the solid electrolyte layer may comprise the polymer solid electrolyte.

[0060] When the positive electrode layer contains a polymer solid electrolyte, the polymer solid electrolyte may be formed on one side of the positive electrode active material layer. When the negative electrode layer contains a polymer solid electrolyte, the polymer solid electrolyte may be formed on one side of the negative electrode active material layer. When the positive electrode layer and / or the negative electrode layer contains a polymer solid electrolyte, the effect of improving the electrical conductivity of the positive electrode and the negative electrode can be exhibited.

[0061] Furthermore, when the solid electrolyte layer contains the polymer solid electrolyte, it can function as an electrolyte by itself.

[0062] In the present invention, the positive electrode included in the all-solid-state battery may include a positive electrode active material layer, and the positive electrode active material layer may be formed on one surface of a positive electrode current collector.

[0063] The positive electrode active material layer includes a positive electrode active material, a binder, and a conductive material.

[0064] The positive electrode active material is not particularly limited as long as it is a material capable of reversibly absorbing and releasing lithium ions. For example, lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), Li[Ni x Co y Mn z M v ]O 2 (wherein M is any one or more elements selected from the group consisting of Al, Ga, and In; 0.3≦x<1.0, 0≦y, z≦0.5, 0≦v≦0.1, and x+y+z+v=1), Li (Li a M b-a-b’ M' b’ )O 2-c A c(wherein 0≦a≦0.2, 0.6≦b≦1, 0≦b'≦0.2, 0≦c≦0.2, M includes Mn and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn, and Ti; M' is at least one selected from the group consisting of Al, Mg, and B; and A is at least one selected from the group consisting of P, F, S, and N), or a compound substituted with one or more transition metals; 1+y Mn 2-y O 4 (where y is 0 to 0.33), LiMnO 3 , LiMn 2 O 3 , LiMnO 2 Lithium manganese oxides such as lithium copper oxide (Li 2 CuO 2 );LiV 3 O 8 , Life 3 O 4 , V 2 O 5 , Cu 2 V 2 O 7 Vanadium oxides such as LiNi 1-y MyO 2 (wherein M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y is 0.01 to 0.3); 2-y M y O 2 (wherein M is Co, Ni, Fe, Cr, Zn or Ta, and y is 0.01 to 0.1) or Li 2 Mn 3 MO 8 Lithium manganese oxides represented by the formula LiMn (where M is Fe, Co, Ni, Cu or Zn); 2 O 4 ;Disulfide compounds;Fe 2 (MoO 4 ) 3 These include, but are not limited to:

[0065] In addition, the positive electrode active material may be included in an amount of 40 to 80 wt % based on the total weight of the positive electrode active material layer. Specifically, the content of the positive electrode active material may be 40 wt % or more or 50 wt % or more, and 70 wt % or less or 80 wt % or less. If the content of the positive electrode active material is less than 40 wt %, the connectivity between the wet positive electrode active material layer and the dry positive electrode active material layer may be insufficient, and if it exceeds 80 wt %, the mass transfer resistance may be large.

[0066] The binder is a component that assists in binding the positive electrode active material to the conductive material and the like and binding to the current collector, and is preferably a rubber such as styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polybutadiene ... The binder may include one or more selected from the group consisting of lylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride, and poly(vinylidene fluoride)-hexafluoropropene. Preferably, the binder may include one or more selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethyl cellulose, polyacrylic acid, lithium polyacrylate, and polyvinylidene fluoride.

[0067] The binder may be included in an amount of 1 wt% to 30 wt% based on the total weight of the positive electrode active material layer, and specifically, the binder content may be 1 wt% or more or 3 wt% or more, and 15 wt% or less or 30 wt% or less. If the binder content is less than 1 wt%, the adhesive strength between the positive electrode active material and the positive electrode current collector may decrease, and if it exceeds 30 wt%, the adhesive strength is improved, but the content of the positive electrode active material may decrease accordingly, and the battery capacity may decrease.

[0068] The conductive material is not particularly limited as long as it prevents side reactions in the internal environment of the all-solid-state battery, does not induce chemical changes in the battery, and has excellent electrical conductivity. Typically, graphite or conductive carbon may be used. For example, graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, denka black, thermal black, channel black, furnace black, lamp black, summer black, and other carbon blacks; carbon-based substances having a graphene or graphite crystal structure; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives; may be used alone or in a mixture of two or more kinds, but are not necessarily limited to these.

[0069] The conductive material may be contained in an amount of 0.5 wt% to 30 wt% based on the total weight of the positive electrode active material layer. Specifically, the content of the conductive material may be 0.5 wt% or more or 1 wt% or more, and 20 wt% or less or 30 wt% or less. If the content of the conductive material is less than 0.5 wt%, the effect of improving electrical conductivity may be difficult to expect, or the electrochemical properties of the battery may be deteriorated, and if the content is more than 30 wt%, the amount of the positive electrode active material may be relatively small, and the capacity and energy density may be reduced. There is no particular limit to the method of incorporating the conductive material into the positive electrode, and a conventional method known in the art, such as coating on the positive electrode active material, may be used.

[0070] The positive electrode current collector supports the positive electrode active material layer and transfers electrons between an external conductor and the positive electrode active material layer.

[0071] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the all-solid-state battery and has high electronic conductivity. For example, the positive electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, palladium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, silver, or the like, or an aluminum-cadmium alloy.

[0072] The positive electrode current collector may have a fine uneven structure or a three-dimensional porous structure on the surface thereof in order to strengthen the bonding force with the positive electrode active material layer, and may have various forms such as a film, a sheet, a foil, a mesh, a net, a porous body, a foam, a nonwoven fabric, etc.

[0073] The positive electrode may be manufactured according to a conventional method, specifically, by mixing a positive electrode active material, a conductive material, and a binder in an organic solvent to prepare a composition for forming a positive electrode active material layer, applying the composition onto a positive electrode current collector, drying the composition, and optionally compressing the composition into a current collector to improve the electrode density. At this time, it is preferable to use an organic solvent that can uniformly disperse the positive electrode active material, the binder, and the conductive material and that can be easily evaporated. Specifically, acetonitrile, methanol, ethanol, tetrahydrofuran, water, isopropyl alcohol, etc. may be used.

[0074] In the present invention, the negative electrode included in the all-solid-state battery may include a negative electrode active material layer, and the negative electrode active material layer may be formed on one surface of a negative electrode current collector.

[0075] The negative electrode active material is lithium (Li + The lithium-containing compound may include a material capable of reversible intercalation or deintercalation of lithium ions, a material capable of reversibly reacting with lithium ions to form a lithium-containing compound, lithium metal, or a lithium alloy.

[0076] The lithium ion (Li + The material capable of reversibly inserting or de-inserting lithium ions (Li) may be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + The material capable of reacting with lithium (Li) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).

[0077] Preferably, the negative electrode active material is lithium metal, and more particularly, may be in the form of a lithium metal thin film or lithium metal powder.

[0078] The negative electrode active material may be included in an amount of 40 to 80 wt % based on the total weight of the negative electrode active material layer. Specifically, the content of the negative electrode active material may be 40 wt % or more or 50 wt % or more, and 70 wt % or less or 80 wt % or less. If the content of the negative electrode active material is less than 40 wt %, the connectivity between the wet negative electrode active material layer and the dry negative electrode active material layer may be insufficient, and if it exceeds 80 wt %, the mass transfer resistance may be large.

[0079] The binder is the same as that described above in the positive electrode active material layer.

[0080] The conductive material is the same as that described above in the positive electrode active material layer.

[0081] The negative electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity, and for example, the negative electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. Similarly to the positive electrode current collector, the negative electrode current collector may be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., with fine irregularities formed on the surface.

[0082] The method for manufacturing the negative electrode is not particularly limited, and the negative electrode may be manufactured by forming a negative electrode active material layer on a negative electrode current collector using a layer or film forming method commonly used in the art. For example, methods such as compression bonding, coating, deposition, etc. may be used. In addition, the negative electrode of the present invention also includes a case where a thin metallic lithium film is formed on a metal plate by initial charging after assembling a battery without a thin lithium film on the negative electrode current collector.

[0083] Battery Module The present invention also provides a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.

[0084] In this case, specific examples of the device include, but are not limited to, power tools that are powered by a battery-type motor; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and the like; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.

[0085] Below, preferred examples are shown to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical spirit of the present invention. Naturally, such changes and modifications also fall within the scope of the appended claims.

[0086] In the following Examples and Comparative Examples, polymer solid electrolytes were produced according to the compositions shown in Table 1 below.

[0087] [Table 1]

[0088] Example 1 Aquivion-Li (Merck, 25% aqueous solution, CAS No. 1687740-67-5) was added as a single ion conductor to liquid polyethylene glycol-polyhedral oligomeric silsesquioxane (PEG-POSS) and mixed to obtain a solution for forming a polymer solid electrolyte. At this time, the weight ratio of the single ion conductor to PEG-POSS was set to 1:2. The Aquivion-Li reacts with the sulfonic acid group (-SO ) contained in the perfluorosulfonic acid polymer. 3 It is a single-ion conductor in which the hydrogen of lithium cation (Li+) is replaced by a lithium cation (H).

[0089] The polymer solid electrolyte forming solution was applied onto a SUS foil with a doctor blade to form a coating film.

[0090] Thereafter, the mixture was heat-treated at 100° C. for 1 day by vacuum drying to produce a polymer solid electrolyte.

[0091] Example 2 A polymer solid electrolyte was prepared in the same manner as in Example 1, except that the liquid PEG-POSS was mixed with a lithium salt LiTFSI in a weight ratio of 1:0.4 to dissociate the lithium salt, and then SIC was mixed.

[0092] Example 3 A polymer solid electrolyte was prepared in the same manner as in Example 2, except that the weight ratio of SIC to liquid phase PEG-POSS was 1:1.

[0093] Comparative Example 1 A liquid electrolyte in the form of a SIC solution was obtained in the same manner as in Example 1, except that no liquid PEG-POSS was used and no drying was performed. Aquivion-Li (Merck, 25% aqueous solution) used as the SIC is itself in the form of an aqueous solution, and therefore becomes a liquid electrolyte without a drying step.

[0094] Comparative Example 2 A solid electrolyte was obtained in the same manner as in Example 1, except that liquid phase PEG-POSS was not used.

[0095] Comparative Example 3 A polymer solid electrolyte was prepared in the same manner as in Example 2, except that the weight ratio of SIC to liquid phase PEG-POSS was 1:3.

[0096] Experimental example 1: Evaluation of the physical properties of polymer solid electrolyte The polymer solid electrolytes prepared in the examples and comparative examples were tested for ion conductivity and membrane state by the following methods, and the results are shown in Table 2 below.

[0097] (1) Ionic conductivity 1.7671cm 2 The solid polymer electrolyte was punched out into a circle of the same size, and the punched solid polymer electrolyte was placed between two pieces of stainless steel (SUS) to manufacture a coin cell. An AC voltage was applied to the coin cell at room temperature, and the application conditions were set to an amplitude range of 500KHz to 20MHz for the measurement frequency, and the impedance was measured using a VMP3 manufactured by BioLogic. Using the following formula 1, the resistance (Rb) of the solid polymer electrolyte was calculated from the intersection point where the semicircle or straight line of the measured impedance locus intersected with the actual contraction, and the ionic conductivity (σ) was calculated from the area (A) and thickness (t) of the solid polymer electrolyte.

[0098]

number

[0099] σ: Ionic conductivity of polymer solid electrolyte Rb:Resistance A: Size of polymer solid electrolyte t: Thickness of the polymer solid electrolyte

[0100] (2) Membrane state The state of the polymer solid electrolyte membrane was observed with the naked eye to judge whether or not it was formed into a film.

[0101] [Table 2] As shown in Table 2, in Example 1, a polymer solid electrolyte having a solid-phase membrane shape and excellent ion conductivity was obtained by using a single ion conductor and liquid-phase PEG-POSS as raw materials and subjecting them to a drying process.

[0102] In Examples 2 and 3, a lithium salt was added to Example 1, and it is clear that the ionic conductivity was improved by the lithium salt.

[0103] On the other hand, in Comparative Example 1, a liquid phase electrolyte was produced simply by applying a single ion conductor that was itself in the form of an aqueous solution.

[0104] In Comparative Example 2, a drying step was added to Comparative Example 1, and a solid-phase membrane was obtained, but it was found that the ion conductivity was low.

[0105] In addition, in Comparative Example 3, liquid phase PEG-POSS was used in an excessive amount compared to the single ion conductor, and a liquid phase electrolyte was produced, and phase separation was also observed.

[0106] In this way, the single ion conductor itself contains Li ions in the form of a polymer solid electrolyte, so it can exhibit the appropriate ion conductivity required for the electrolyte, and when liquid phase PEG-POSS is added at an appropriate weight ratio, the fluidity of the polymer chain improves, improving the ion conductivity. In addition, when a lithium salt is added, the ion conductivity can be further improved.

[0107] Although the present invention has been described above using limited examples and drawings, the present invention is not limited thereto, and it is obvious that various modifications and variations can be made by a person having ordinary knowledge in the technical field to which the present invention pertains within the technical spirit of the present invention and the equivalent scope of the claims described below. [Explanation of symbols]

[0108] 1:Polymer solid electrolyte 10: Single ion conductor (SIC) 20: Liquid-phase polyhedral oligomeric silsesquioxanes (POSS)

Claims

1. A polymer solid electrolyte comprising a single ion conductor (SIC) and a liquid phase polyhedral oligomeric silsesquioxane (POSS).

2. The polymer solid electrolyte according to claim 1 , wherein the liquid-phase polyhedral oligomeric silsesquioxane is contained in an internal space formed by the polymer chains contained in the single-ion conductor.

3. The single ion conductor includes a perfluorosulfonic acid (PFSA)-based polymer, and a sulfonic acid group (-SO 3 The hydrogen of the lithium cation (Li + 2. The polymer solid electrolyte according to claim 1, wherein the polymer solid electrolyte has a structure substituted with .

4. The polymer solid electrolyte further comprises a lithium salt, The lithium salt is (CF 3 SO 2 ) 2 NLi (LiTFSI), (FSO 2 ) 2 NLi (LiFSI), LiNO 3 , LiOH, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 C 10 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, LiSCN and LiC(CF 3 SO 2 ) 3 The polymer solid electrolyte according to claim 1, comprising at least one selected from the group consisting of:

5. 2. The polymer solid electrolyte according to claim 1, wherein the weight ratio of the single ion conductor to the liquid phase polyhedral oligomeric silsesquioxane is 1:1 to 1:

2.

6. The polymer solid electrolyte according to claim 1 , wherein the polymer solid electrolyte is in the form of a free-standing film.

7. The polymer solid electrolyte of claim 1 , further comprising a liquid electrolyte.

8. (S1) forming a polymer solid electrolyte forming solution containing a single ion conductor (SIC) and a liquid-phase polyhedral oligomeric silsesquioxane (POSS); (S2) applying the polymer solid electrolyte forming solution onto a substrate to form a coating film; and (S3) a step of drying the coating film.

9. The method for producing a polymer solid electrolyte according to claim 8 , wherein a lithium salt is further added in the step of forming the polymer solid electrolyte forming solution.

10. An all-solid-state battery comprising the polymer solid electrolyte according to any one of claims 1 to 7.

11. The all-solid-state battery includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, 11. The all-solid-state battery according to claim 10, wherein at least one of the positive electrode layer, the negative electrode layer, and the solid electrolyte layer comprises the polymer solid electrolyte.

12. A battery module comprising the all-solid-state battery according to claim 10.

Citation Information

Patent Citations

  • Proton conductive membrane and fuel cell using it

    JP2005339961A

  • Fluorine-based nanocomposite membrane containing polyhedral oligomeric silsesquioxane having proton donor and proton acceptor, and method for producing the same

    JP2018525778A

  • Separator and lithium secondary battery including the same

    JP2020536352A

  • Solid polymer electrolyte composition and lithium secondary battery including the same

    US20150244025A1

  • KR2017-0046995